2009
DOI: 10.1211/jpp.61.06.0001
|View full text |Cite
|
Sign up to set email alerts
|

Sonophoresis: recent advancements and future trends

Abstract: Objectives Use of ultrasound in therapeutics and drug delivery has gained importance in recent years, evident by the increase in patents filed and new commercial devices launched. The present review discusses new advancements in sonophoretic drug delivery in the last two decades, and highlights important challenges still to be met to make this technology of more use in the alleviation of diseases. Key findings Phonophoretic research often suffers from poor calibration in terms of the amount of ultrasound energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 138 publications
(177 reference statements)
0
56
0
1
Order By: Relevance
“…Recent studies have shown that ultrasound can increase up to 5,000 times the ability of protein the size of insulin to penetrate the skin. Using a transdermal patch design in conjunction with ultrasound may provide an improved method for Insulin delivery [24,25].…”
Section: Sonophoresismentioning
confidence: 99%
“…Recent studies have shown that ultrasound can increase up to 5,000 times the ability of protein the size of insulin to penetrate the skin. Using a transdermal patch design in conjunction with ultrasound may provide an improved method for Insulin delivery [24,25].…”
Section: Sonophoresismentioning
confidence: 99%
“…With this technique the ultrasound is used to move molecular drugs through intact living skin and into the soft tissue 7 . It is one of the most promising novel drug delivery system and has been shown to enhance the skin penetration and release rate of number of drugs that have poor absorption or permeation profiles through the skin.…”
Section: Issn: 0975-8232mentioning
confidence: 99%
“…DISCUSSION: Various hypotheses have been used to explain sonophoretic enhancement, the way of how US modifies and improve the permeation could not be answered by using a single mechanism because many different potentially modulating physical situation are generated simultaneously by ultrasonic wave, and the theoretical and experimental basis of the intricate mechanism is in its infancy 7 . Thermal effect and cavitation are the most significant mechanisms used to explain the effect of US 18,19,20,21 .…”
Section: Figure 3: Effect Of Low Frequency Us At Different Amplitudesmentioning
confidence: 99%
“…Recently, ultrasonic irradiation has been applied as a trigger to induce preparation, modification, and degradation of polymers as observed in recent reviews [17][18][19][20][21]. The degradation of polyethylenes [22,23], polyamides [24], polyacrylates [25,26], and epoxy-amine thermosets [27] were reported.…”
Section: Introductionmentioning
confidence: 99%